Quantum dot, wavelength conversion material, backlight source, image display device and method for manufacturing quantum dot

By introducing different metal elements into the core-shell structure of quantum dots and controlling their molar ratio and adsorption amount, the problems of particle size control and emission wavelength adjustment in the prior art are solved, and efficient emission wavelength control and high luminescence are achieved efficiency.

CN113710615BActive Publication Date: 2024-12-13SHIN ETSU CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080030274.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-04-26
Filing Date
2020-02-10
Publication Date
2024-12-13
Estimated Expiration
2040-02-10

AI Technical Summary

Technical Problem

The prior art is difficult to finely control the particle size and emission wavelength of quantum dots, resulting in widening of luminescence peaks, affecting the color reproducibility and luminescence efficiency of wavelength conversion materials.

Method used

Quantum dots with core-shell structures, in which there are different metal elements at the interface between the core particles and the shell layer. The molar ratio of the third metal element is less than 10% relative to the first metal element in the core particles. By controlling the third metal element Adsorption amount and reaction temperature to adjust the emission wavelength.

Benefits of technology

The fine control of the emission wavelength is achieved, the luminous characteristics and luminous efficiency are improved, and the high color reproducibility and high luminous efficiency of the wavelength conversion material are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113710615B_ABST
    Figure CN113710615B_ABST
Patent Text Reader

Abstract

The present invention is a quantum dot, which is a quantum dot as a crystalline nanoparticle phosphor, wherein the quantum dot has a core-shell structure, the core-shell structure includes a core particle containing a first metal element and a shell layer containing a second metal element, and a third metal element different from the first metal element and the second metal element exists at the interface between the core particle and the shell layer, and the amount of the third metal element is 10% or less relative to the amount of the first metal element contained in the core particle in terms of molar ratio. Thus, a quantum dot having excellent controllability of emission wavelength and high luminescence characteristics and luminescence efficiency is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to quantum dots, wavelength conversion materials, backlight sources, image display devices and methods for manufacturing quantum dots. Background Art

[0002] Semiconductor crystal particles with a particle size of nanometers are called quantum dots. Since the excitons generated by light absorption are confined to the nanometer area, the energy level of the semiconductor crystal particles becomes discrete. In addition, its band gap changes due to the particle size. Due to these effects, the fluorescence of quantum dots is brighter and more efficient than that of ordinary phosphors, and its emission peak is sharp. In addition, due to the characteristic that the band gap changes due to its particle size, quantum dots have the characteristic of being able to control the emission wavelength, and their application as wavelength conversion materials for solid lighting or displays is expected. For example, by using quantum dots as wavelength conversion materials in displays, a wider color gamut and lower power consumption can be achieved than existing phosphor materials.

[0003] As a method for installing quantum dots as wavelength conversion materials, Patent Document 1 proposes a method of dispersing quantum dots in a resin material, laminating the resin material containing quantum dots on a transparent film, and installing it in a backlight source as a wavelength conversion film (Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application No. 2013-544018

[0007] Patent Document 2: Japanese Patent Application No. 2010-535262 Summary of the invention

[0008] Technical Problems to be Solved by the Invention

[0009] However, since the band gap of quantum dots changes with particle size and the emission wavelength shifts with particle size, there is a problem that the size of the particles must be controlled at the nanometer level in order to obtain the target wavelength, and the uneven particle size causes the emission peak to become wider. Quantum dots are usually synthesized in the form of colloids by reacting precursors in a solution, but it is not easy to control the particle size so precisely at the nanometer level in a solution reaction. Furthermore, when mass production is implemented during industrialization, there are also problems with uneven concentration and temperature distribution of precursors in the solution reaction, making it even more difficult to control the particle size.

[0010] In addition, when the emission wavelength is usually controlled, for example, when the emission wavelength is to be shifted to the long wavelength side, there is a method of increasing the particle size by lengthening the reaction time or increasing the reaction temperature in the synthesis of the core particles. However, such a method will cause uneven particle growth due to the prolonged reaction time, thus causing the particle size distribution to become wider, the luminous waveform to become wider, and become the cause of reduced color reproducibility when used as a wavelength conversion material. In addition, since the speed of the chemical reaction becomes faster due to the increase in the reaction temperature, it becomes difficult to control the nucleation reaction and the nucleus growth reaction, resulting in the generated particles being prone to unevenness, and the luminous peak is also widened, and becomes the cause of reduced color reproducibility when used as a wavelength conversion material.

[0011] On the other hand, when the emission wavelength is to be shifted to the short wavelength side, in contrast to the above, there is a method of reducing the particle size by shortening the reaction time or lowering the reaction temperature in the synthesis of the core particles. In such a method, there is also a problem that the crystallinity of the generated core particles is reduced due to the reduction of the reaction temperature, crystal defects are easily generated, and the light efficiency is reduced.

[0012] In order to solve such a problem, Patent Document 2 studies a method of synthesizing a molecular cluster composed of constituent elements of quantum dots as a seed for particle growth (Patent Document 2).

[0013] However, the method described in Patent Document 2 uses compounds such as organic metal complexes as molecular clusters, so it is difficult to arbitrarily change the composition or ratio. In addition, since the reaction temperature depends on the decomposition temperature or reactivity of the molecular cluster, there is a limitation in the control of the emission wavelength based on the particle size control.

[0014] The present invention is implemented to solve the above problems, and its purpose is to provide a quantum dot with excellent controllability of emission wavelength and high luminous properties and luminous efficiency. In addition, its purpose is to provide a method for manufacturing a quantum dot that is easy to control the emission wavelength while having high luminous properties and luminous efficiency.

[0015] Technical means to solve technical problems

[0016] The present invention is implemented to achieve the above-mentioned purpose. The present invention provides a quantum dot, which is a quantum dot as a crystalline nanoparticle phosphor, wherein the quantum dot has a core-shell structure, and the core-shell structure includes a core particle containing a first metal element and a shell layer containing a second metal element. A third metal element different from the first metal element and the second metal element exists at the interface between the core particle and the shell layer, and the amount of the third metal element is less than 10% relative to the amount of the first metal element contained in the core particle in molar ratio.

[0017] According to such quantum dots, the emission wavelength can be easily controlled and the controllability of the emission wavelength is excellent, and at the same time, high light-emitting characteristics and light-emitting efficiency are provided.

[0018] At this time, the third metal element can be set to at least one selected from Cu, Ag, Mn, Al, Ga, Ge, Si, Bi, Cs, Sn, Fe, Co, Ni, Cr, Li, Na, K, Ca, Mg, and Mo.

[0019] As a result, the emission wavelength can be easily controlled and the controllability of the emission wavelength is excellent, and at the same time, higher light-emitting characteristics and light-emitting efficiency are achieved.

[0020] In this case, the quantum dots can be made to contain no Cd (cadmium).

[0021] Therefore, it does not contain harmful substances and has a small burden on the environment.

[0022] At this time, the core particles can be set to particles selected from InP, ZnSe, ZnTe, CuInS2, and AgInS2.

[0023] Therefore, it is more suitable for optical devices in the visible light region such as displays or lighting.

[0024] In this case, a wavelength conversion material containing the quantum dots of the present invention, a backlight including the wavelength conversion material, and an image display device including the backlight can be produced.

[0025] This makes it possible to provide a wavelength conversion material, a backlight, and an image display device that have high luminous efficiency and excellent color reproducibility.

[0026] In addition, a method for manufacturing quantum dots can be provided, which is a method for manufacturing quantum dots as a crystalline nanoparticle phosphor, wherein the quantum dots have a core-shell structure, and the core-shell structure includes a core particle containing a first metal element and a shell layer containing a second metal element, wherein the method for manufacturing quantum dots includes: a process of forming the core particle; a process of adsorbing a third metal element different from the first metal element and the second metal element on the surface of the core particle; and a process of forming the shell layer on the third metal element on the surface of the core particle, and in the process of adsorbing the third metal element, the amount of the third metal element relative to the amount of the first metal element contained in the core particle is set to less than 10% in molar ratio.

[0027] This makes it possible to produce quantum dots that can easily control the emission wavelength and have high luminescence properties and luminescence efficiency.

[0028] In this case, the reaction temperature of the step of adsorbing the third metal element can be set to be lower than the reaction temperature of the step of forming the core particles.

[0029] This makes it possible to produce quantum dots with higher light-emitting properties and light-emitting efficiency.

[0030] Effects of the Invention

[0031] As described above, according to the quantum dots of the present invention, it is easy to control the emission wavelength and the controllability of the emission wavelength is excellent, and at the same time, it has high luminescence characteristics and luminescence efficiency. In addition, according to the method for manufacturing quantum dots of the present invention, it is possible to manufacture quantum dots that are easy to control the emission wavelength and also have high luminescence characteristics and luminescence efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The quantum dots of the present invention are shown. DETAILED DESCRIPTION

[0033] The present invention will be described in detail below, but the present invention is not limited thereto.

[0034] As described above, a quantum dot having excellent controllability of emission wavelength and high light-emitting properties and light-emitting efficiency is sought.

[0035] The inventors of the present application have repeatedly conducted in-depth studies on the above-mentioned technical problems, and as a result, they have found that by using the following quantum dots, they can form quantum dots that have excellent controllability of emission wavelength and at the same time have high luminescence characteristics and luminescence efficiency, thereby completing the present invention: a quantum dot as a crystalline nanoparticle phosphor, the quantum dot having a core-shell structure, the core-shell structure comprising a core particle comprising a first metal element and a shell layer comprising a second metal element, a third metal element different from the first metal element and the second metal element existing at the interface between the core particle and the shell layer, and the amount of the third metal element relative to the amount of the first metal element contained in the core particle, in molar ratio, is less than 10%.

[0036] In addition, a method for producing quantum dots that have high luminescent properties and luminescent efficiency and that can easily control the emission wavelength is also sought.

[0037] The inventors of the present application have repeatedly conducted in-depth studies on the above-mentioned technical problems, and as a result, they have found that, through the following method for manufacturing quantum dots, it is possible to manufacture quantum dots having high luminescence characteristics and luminescence efficiency, and at the same time it is easy to control the emission wavelength, thereby completing the present invention: a method for manufacturing quantum dots as crystalline nanoparticle phosphors, the quantum dots having a core-shell structure, the core-shell structure comprising a core particle containing a first metal element and a shell layer containing a second metal element, the method for manufacturing quantum dots comprising: a process for forming the core particle; a process for adsorbing a third metal element different from the first metal element and the second metal element on the surface of the core particle; and a process for forming the shell layer on the third metal element on the surface of the core particle, in the process for adsorbing the third metal element, the amount of the third metal element relative to the amount of the first metal element contained in the core particle is set to be less than 10% in molar ratio.

[0038] like Figure 1 As shown, the quantum dot 10 of the present invention has a core-shell structure (also referred to as a "core-shell quantum dot"), the core-shell structure comprising a core particle 1 containing a first metal element and a shell layer 2 containing a second metal element, and a third metal element 4 different from the first metal element contained in the core particle 1 and the second metal element contained in the shell layer 2 exists at an interface 3 (also referred to as a "core-shell interface") between the core particle 1 and the shell layer 2. In addition, the amount of the third metal element 4 relative to the amount of the first metal element contained in the core particle 1 is less than 10% by molar ratio.

[0039] The first metal element, the second metal element, and the third metal element may each be not only one metal element but may also include a plurality of metal elements.

[0040] The composition of the quantum dots is not particularly limited and can be appropriately selected according to the target wavelength conversion material and optical element. As the composition of the quantum dots, compositions containing cadmium such as CdSe or CdS are generally used, but since cadmium is a harmful substance and its use is strictly restricted by regulations, compositions not containing cadmium are preferred.

[0041] As the composition of the core particles of the core-shell quantum dots, there can be cited II-IV semiconductors, III-V semiconductors, II-VI semiconductors, I-III-VI semiconductors, II-IV-V semiconductors, IV semiconductors, perovskite semiconductors, etc. Specifically, there can be cited InP, InSb, AlP, AlSb, ZnSe, ZnS, ZnTe, Zn3P2, GaP, GaSb, CuInSe2, CuInS2, CuInTe2, CuGaSe2, CuGaS2, CuGaTe2, CuAlSe2, CuAlS2, CuAlTe2, AgInSe2, AgInS2, AgInTe2, AgGaSe2, AgGaS2, AgGaTe2, Si, Ge, graphene, CsPbCl3, CsPbBr3, CsPbI3, CH3NH3PbCl3 and mixed crystals thereof. If the target optical element is an optical device in the visible light region such as a display or lighting, InP, ZnTe, ZnSe, AgInS2, CuInS2 and mixed crystals thereof are particularly preferred in consideration of the emission wavelength region.

[0042] As the composition of the shell layer of the core-shell quantum dots, ZnSe, ZnS, AlP, AlN, GaN, Ga2S3, MgSe, MgS, etc. can be cited. The shell layer can be one layer, or two or more layers, and can be appropriately changed according to the composition or purpose of the core particle.

[0043] The size and shape of the core particle and the shell layer are not particularly limited and can be appropriately selected according to the target emission wavelength and characteristics.

[0044] In the core-shell quantum dots, by adding a third metal element different from the first metal element contained in the core particle and the second metal element contained in the shell layer to the core-shell interface, the third metal element can be partially filled in the lattice defects such as dangling bonds generated by the lattice mismatch at the core-shell interface to suppress the defects, and the third metal element can be used to compensate for the charges generated by the defects, thereby improving the luminous efficiency. In addition, the energy level of the core-shell interface changes according to the composition of the core particle and the combination of the third metal element, so that the emission wavelength can be shifted to a short wavelength or a long wavelength without changing the particle size of the quantum dots, thereby controlling the emission wavelength.

[0045] As the third metal element different from the metal elements contained in the core particles and the shell layer, it can be appropriately selected from Cu, Ag, Mn, Al, Ga, Ge, Si, Bi, Cs, Sn, Fe, Co, Ni, Cr, Li, Na, K, Ca, Mg, and Mo according to the composition and target characteristics of the quantum dots. The third metal element can be one or a combination of multiple metal elements.

[0046] As a method for adsorbing the third metal element to the core particles, there is a method of dissolving the halide or acetate, carboxylate, organic metal complex and other compounds of each metal element as a precursor in an organic solvent, and adding it dropwise to a solution dispersed with core particles. The types or solvents of these compounds are not particularly limited and can be appropriately selected according to the material system and reaction conditions. The reaction temperature when the third metal element is adsorbed to the core particles is not particularly limited, but it is preferably a temperature below the reaction temperature of the core particles that suppresses the change in the characteristics of the particle size of the core particles in the reaction of the third metal element. In addition, the reaction time can be appropriately selected according to the reactivity or target characteristics of the precursor compound.

[0047] The molar ratio of the amount of the third metal element added at the core-shell interface to the first metal element constituting the core particle is set to less than 10%. This is because if the amount added is greater than 10%, the following problems will arise: byproducts of the third metal element are produced, or the third metal element itself produces new particles, or the third metal element is excessively absorbed by the core surface, causing the energy level of the quantum dots to change significantly, thereby causing the luminescence characteristics to deteriorate, or it is difficult to form a shell on the surface. In addition, the lower limit of the third metal element is not particularly limited, and it can be the planned addition amount, but it is preferably set to more than 0.1% (molar ratio). When it is an amount that is inevitably present, the effect of the present invention cannot be exerted.

[0048] The method for manufacturing quantum dots of the present invention comprises a step of forming core particles, a step of adsorbing a third metal element different from the first metal element contained in the core particles and the second metal element contained in the shell layer on the surface of the core particles, and a step of forming a shell layer on the third metal element on the surface of the core particles, and the amount of the third metal element is set to 10% or less relative to the amount of the first metal element contained in the core particles in terms of molar ratio. In addition, the reaction temperature of the step of adsorbing the third metal element is preferably set to be lower than the reaction temperature of the step of forming the core particles.

[0049] There is no particular restriction on the other various conditions in the method for manufacturing the above-mentioned quantum dots, and they can be appropriately selected according to their composition or target luminescent properties. Further, the surface of the quantum dots may also have a covering layer of organic molecules or inorganic molecules or polymers, and there is no restriction on their structure. In addition, the thickness of the covering layer can also be appropriately selected according to the purpose. Although there is no particular restriction on the thickness of the covering layer, it is desirable to have a thickness that makes the particle size of the quantum dots less than 100nm. If the thickness of the covering layer is within such a range, it has a more stable transmittance due to the more stable dispersibility. In addition, such quantum dots are less likely to condense.

[0050] As the covering layer, examples include organic molecules such as stearic acid, oleic acid, palmitic acid, dimercaptosuccinic acid, oleylamine, hexadecylamine, octadecylamine, 1-dodecylmercaptan, etc.; or polymers such as polyvinyl alcohol or polyvinyl pyrrolidone, polysilsesquioxane, poly(methyl methacrylate), polyacrylonitrile, polyethylene glycol, etc.; inorganic molecules such as silicon dioxide or aluminum oxide, titanium dioxide, zirconium oxide, zinc oxide, gallium oxide, etc.

[0051] In addition, a wavelength conversion material can be obtained from the quantum dots of the present invention. As the wavelength conversion material, uses such as wavelength conversion films or color filters can be listed, but are not limited to these uses. The wavelength conversion material of the present invention can obtain a wavelength conversion material having a target emission wavelength, good color reproducibility, and good luminous efficiency.

[0052] The wavelength conversion film can be obtained by mixing the quantum dots of the present invention with a resin so that the quantum dots are dispersed in the resin. In this process, the quantum dots dispersed in the solvent are added to the resin and mixed, so that they can be dispersed in the resin. In addition, the solvent is removed, and the powdered quantum dots are added to the resin and kneaded, thereby dispersing them in the resin. Alternatively, there is a method of polymerizing monomers or oligomers as resin components under the condition of coexistence with quantum dots. There is no particular limitation on the method of dispersing quantum dots in the resin, and it can be appropriately selected according to the purpose.

[0053] The solvent for dispersing quantum dots and the resin used can be compatible without any particular restrictions. In addition, the resin material is not particularly limited, and silicone resin, acrylic resin, epoxy resin, urethane resin, etc. can be appropriately selected according to the required properties. In order to improve the efficiency as a wavelength conversion material, it is expected that the transmittance of these resins is high, and it is particularly expected that the transmittance is 80% or more.

[0054] In addition, it may also contain substances other than quantum dots, and as a light scatterer, it may contain microparticles such as silicon dioxide or zirconium oxide, aluminum oxide, titanium dioxide, etc., and it may also contain inorganic phosphors or organic phosphors. As inorganic phosphors, YAG, LSN, LYSN, CASN, SCASN, KSF, CSO, β-SIALON, GYAG, LuAG, SBCA may be cited; as organic phosphors, perylene derivatives, anthraquinone derivatives, anthracene derivatives, phthalocyanine derivatives, anthocyanin derivatives, dioxazine derivatives, benzoxazinone derivatives, coumarin derivatives, quinophthalone derivatives, benzoxazole derivatives, pyrazoline derivatives, etc. may be cited.

[0055] The method for preparing the wavelength conversion material of the present invention is not particularly limited and can be appropriately selected according to the purpose. For example, the wavelength conversion material can be obtained by applying a resin composition having quantum dots dispersed in the resin to a transparent film such as PET or polyimide, curing it, and laminating it.

[0056] When being coated on transparent film, can use spraying (spray) or inkjet (inkjet) etc. spraying method, spin coating method or rod coating method, scraper method or gravure printing method or offset printing method, can form resin layer by coating.In addition, the thickness of resin layer and transparent film is not particularly limited, can be appropriately selected according to purpose.

[0057] As one of the embodiments of the wavelength conversion material of the present invention, a backlight source in which the wavelength conversion film is arranged on a light guide surface combined with a blue LED can be cited. In addition, as another embodiment, an image display device in which the wavelength conversion film is arranged between a light guide surface combined with a blue LED and a liquid crystal display panel can be cited. In these embodiments, the wavelength conversion film absorbs at least a portion of the blue light which is the primary light and serves as the light source, and releases secondary light having a longer wavelength than the primary light, thereby being able to convert the light into light having an arbitrary wavelength distribution depending on the emission wavelength of the quantum dots.

[0058] Example

[0059] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited thereto.

[0060] In addition, regarding the evaluation of the fluorescent emission characteristics of the produced quantum dots, the emission characteristics were measured using a quantum efficiency measurement system (QE-2100 manufactured by OTSUKA ELECTRONICS CO., LTD.) with an excitation wavelength of 450 nm.

[0061] (Comparative Example 1)

[0062] (Step 1: Synthesis of InP Core Particles)

[0063] In a 100 mL three-necked flask, 10 mL of 1-octadecene as a solvent, 200 mg of indium acetate, and 450 mg of myristic acid were added, and degassed at 120°C for 2 hours. After degassing, nitrogen was sealed in the flask, and the reaction was carried out in a state of isolation from oxygen. The solution was heated to 280°C, and 1.5 mL of tris(trimethylsilyl)phosphine diluted 10 times with 1-octadecene was quickly added to the stirring solution, and reacted at 280°C for 20 minutes to synthesize InP core particles.

[0064] (Step 2: Formation of ZnS Shell Layer)

[0065] 36 mg of sulfur powder was added to 6 mL of trioctylphosphine, heated to 150°C and stirred to dissolve the sulfur powder to prepare a sulfur solution. 270 mg of anhydrous zinc acetate, 2 mL of oleic acid and 1 mL of oleylamine were added to 7 mL of 1-octadecene, and degassed at 150°C to dissolve the anhydrous zinc acetate to prepare a zinc solution. Next, the solution of the InP core particles obtained in step 1 was maintained at 280°C, and the sulfur solution was added dropwise thereto and stirred for 30 minutes. The solution temperature was further set to 300°C, and the zinc solution was added dropwise and reacted at 300°C for 60 minutes. Thus, an InP / ZnS core-shell quantum dot solution was obtained.

[0066] Acetone was added to the quantum dot solution after the reaction in a 5-fold volume ratio to precipitate the quantum dots. The solution was centrifuged at 10,000 rpm for 10 minutes using a centrifuge, and the recovered precipitate was dispersed again in toluene to purify the quantum dots.

[0067] The light emission characteristics of the quantum dots obtained in this manner were measured. As a result, the emission wavelength was 521 nm, the half-value width of the light emission was 43 nm, and the internal quantum efficiency was 62%.

[0068] (Example 1)

[0069] After the same process 1 as in Comparative Example 1, 20 mg of copper acetate (I), 6 mL of oleic acid, and 14 mL of 1-octadecene were mixed and degassed at 150 ° C for 2 hours to prepare a copper solution dissolved with copper acetate. 1 mL of this copper solution was added dropwise to a solution of core particles synthesized by the same process 1 as in Comparative Example 1, while the temperature of the solution was maintained at 200 ° C, and stirred at 200 ° C for 30 minutes to adsorb Cu atoms on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 2 was performed to obtain InP / ZnS quantum dots to which Cu was added at the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and as a result, the emission wavelength was 536 nm, the half-value width of the luminescence was 43 nm, and the internal quantum efficiency was 72%.

[0070] (Example 2)

[0071] In the same manner as in Example 1, after the same process 1 as in Comparative Example 1, 20 mg of silver acetate (I), 6 mL of oleic acid, and 14 mL of 1-octadecene were mixed and degassed at 150° C. for 2 hours to prepare a silver solution in which silver acetate was dissolved. 5 mL of this silver solution was added dropwise to a solution of core particles synthesized in the same process 1 as in Comparative Example 1, while the temperature of the solution was maintained at 200° C. and stirred at 200° C. for 30 minutes to allow Ag atoms to be adsorbed on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 2 was performed to obtain InP / ZnS quantum dots to which Ag was added at the core-shell interface. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 592 nm, the half-value width of the luminescence was 44 nm, and the internal quantum efficiency was 75%.

[0072] (Example 3)

[0073] In the same manner as in Example 1, after the same process 1 as in Comparative Example 1, 42 mg of calcium stearate, 12 mg of anhydrous gallium chloride (III), 1 mL of oleylamine, 1 mL of oleic acid, and 8 mL of 1-octadecene were mixed and degassed at 170°C for 2 hours to prepare a solution in which calcium stearate and anhydrous gallium chloride were dissolved. 1 mL of this solution was added dropwise to a solution of core particles synthesized in the same process 1 as in Comparative Example 1, while the temperature of the solution was maintained at 200°C and stirred at 200°C for 30 minutes to allow Ca and Ga atoms to adsorb on the surface of the core particles. Afterwards, the same process as in the above process 2 was performed to obtain InP / ZnS quantum dots with Ca and Ga added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 495 nm, the half-value width of the luminescence was 39 nm, and the internal quantum efficiency was 69%.

[0074] (Example 4)

[0075] In the same manner as in Example 1, after the same process 1 as in Comparative Example 1, 100 mg of potassium stearate, 95 mg of sodium stearate, and 10 mL of 1-octadecene were mixed and degassed at 180 ° C for 2 hours to prepare a solution in which potassium stearate and sodium stearate were dissolved. 1 mL of this solution was added dropwise to a solution of core particles synthesized in the same process 1 as in Comparative Example 1, while the temperature of the solution was maintained at 200 ° C and stirred at 200 ° C for 30 minutes to adsorb K and Na atoms on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 2 was performed to obtain InP / ZnS quantum dots to which K and Na were added at the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and as a result, the emission wavelength was 515 nm, the half-value width of the luminescence was 42 nm, and the internal quantum efficiency was 70%.

[0076] (Example 5)

[0077] In the same manner as in Example 1, after the same process 1 as in Comparative Example 1, 22 mg of anhydrous magnesium chloride (II), 1 mL of oleylamine, 1 mL of oleic acid, and 8 mL of 1-octadecene were mixed and degassed at 120 ° C for 2 hours to prepare a solution in which anhydrous magnesium chloride (II) was dissolved. 2 mL of this solution was added dropwise to a solution of core particles synthesized in the same process 1 as in Comparative Example 1, while the temperature of the solution was maintained at 200 ° C and stirred at 200 ° C for 30 minutes to adsorb Mg atoms on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 2 was performed to obtain InP / ZnS quantum dots to which Mg was added at the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and as a result, the emission wavelength was 507 nm, the half-value width of the luminescence was 40 nm, and the internal quantum efficiency was 66%.

[0078] (Example 6)

[0079] In the same manner as in Example 1, after the same process 1 as in Comparative Example 1, a solution of 5 mL of germanium (IV) chloride, 1 mL of oleylamine, and 4 mL of 1-octadecene was prepared. 5 mL of this solution was added dropwise to a solution of core particles synthesized in the same process 1 as in Comparative Example 1, while the temperature of the solution was maintained at 200° C. and stirred at 200° C. for 30 minutes to allow Ge atoms to be adsorbed on the surface of the core particles. Afterwards, the same treatment as in the above-mentioned process 2 was performed to obtain InP / ZnS quantum dots to which Ge was added at the core-shell interface. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 533 nm, the half-value width of the luminescence was 38 nm, and the internal quantum efficiency was 68%.

[0080] (Example 7)

[0081] In addition to changing the temperature when adding the copper solution in Example 1 to 300° C., the reaction was carried out under the same conditions as in Example 1 to obtain InP / ZnS quantum dots with Cu added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 528 nm, the half-value width of the luminescence was 50 nm, and the internal quantum efficiency was 63%.

[0082] (Comparative Example 2)

[0083] InP / ZnS core-shell particles were synthesized under the same conditions except that the synthesis temperature of the core particles in step 1 of Comparative Example 1 was changed to 310° C. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 540 nm, the half-value width of the luminescence was 55 nm, and the internal quantum efficiency was 60%.

[0084] (Comparative Example 3)

[0085] InP / ZnS core-shell particles were synthesized under the same conditions except that the synthesis temperature of the core particles in step 1 of Comparative Example 1 was changed to 250° C. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 508 nm, the half-value width of the luminescence was 45 nm, and the internal quantum efficiency was 53%.

[0086] (Comparative Example 4)

[0087] In the process 1 of comparative example 1, 10mL of 1-octadecene as solvent, 200mg of indium acetate, 450mg of myristic acid and 1mg of copper acetate (I) were added to a 100mL three-necked flask, and degassed for 2 hours at 120°C. After degassed, nitrogen was sealed in the flask, and the reaction was carried out in a state of being isolated from oxygen. The solution was heated to 280°C, and 1.5mL of tris (trimethylsilyl) phosphine diluted 10 times with 1-octadecene was rapidly added to the stirring solution, and reacted at 280°C for 20 minutes to synthesize InP core particles in which Cu atoms were added to the core. For the obtained core particles, a ZnS shell was formed under the same conditions as in the process 2 of comparative example 1. Thus, InP / ZnS quantum dots in which Cu atoms were added to the core particles were obtained. The light emission characteristics of the quantum dots obtained in this manner were measured. As a result, the emission wavelength was 689 nm, the half-value width of the light emission was 77 nm, and the internal quantum efficiency was 70%.

[0088] (Comparative Example 5)

[0089] In addition to changing the amount of silver solution added in Example 2 to 12.6 mL, the reaction was carried out under the same conditions as in Example 2 to obtain InP / ZnS quantum dots with Ag added to the core-shell interface. The luminescence properties of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 618 nm, the half-value width of the luminescence was 52 nm, and the internal quantum efficiency was 70%.

[0090] (Comparative Example 6)

[0091] In addition to changing the amount of copper solution added in Example 1 to 17 mL, the reaction was carried out under the same conditions as in Example 1 to obtain InP / ZnS quantum dots with Cu added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength had two peaks of 510 nm and 644 nm, the half-value widths of the luminescence were 49 nm and 75 nm, respectively, and the total internal quantum efficiency of the two peaks was 56%.

[0092] Table 1 shows the results of Examples 1 to 7 and Comparative Examples 1 to 6.

[0093] [Table 1]

[0094]

[0095] * The reaction temperature when Cu was adsorbed on the core particles was different between Example 1 and Example 7.

[0096] Comparative Examples 1 to 3 had different reaction temperatures when forming core particles.

[0097] By comparing Examples 1 to 7 with Comparative Examples 1 to 6, it can be seen that by adding a third metal element not contained in the core particle and the shell layer to the core-shell interface in an amount (molar ratio) of 10% or less relative to the first metal element contained in the core particle, it is possible to obtain quantum dots that can control the emission wavelength without adjusting the quantum dot diameter, and have high luminescence efficiency and good luminescence characteristics. In addition, by comparing Example 1 with Example 7, it can be seen that Example 1 has better luminescence characteristics. It can be seen that by setting the reaction temperature when the third metal element is adsorbed on the core particle to be lower than the reaction temperature when the core particle is formed, quantum dots with better luminescence characteristics can be obtained.

[0098] (Comparative Example 7)

[0099] (Step 3: Synthesis of ZnSeTe Core Particles)

[0100] To a 100 mL three-necked flask, 20 mL of 1-octadecene as a solvent and 6.5 mL of oleic acid were added, and degassed at 120 ° C for 30 minutes. After degassing, nitrogen was sealed in the flask, and the reaction was carried out in a state of isolation from oxygen. In addition, 79 mg of selenium powder and 96 mg of tellurium powder were added to 20 mL of trioctylphosphine, heated to 150 ° C and stirred to dissolve the selenium powder and tellurium powder to prepare a selenium-tellurium solution. 10 mL of the selenium-tellurium solution was mixed with 0.11 mL of diethyl zinc under a nitrogen atmosphere, and the mixed solution was added dropwise to a flask heated to 250 ° C, and reacted at 250 ° C for 30 minutes to synthesize ZnSeTe core particles.

[0101] (Step 4: Formation of ZnS Shell Layer)

[0102] 0.07 mL of diethyl zinc, 0.16 mL of 1-dodecyl mercaptan and 6 mL of 1-octadecene were mixed, and the mixed solution was added dropwise to the solution of ZnSeTe core particles obtained in the above step 3 at a temperature of 240° C. and stirred for 30 minutes. Thus, a ZnSeTe / ZnS type quantum dot solution was obtained.

[0103] Acetone was added to the quantum dot solution after the reaction in a 5-fold volume ratio to precipitate the quantum dots. The solution was centrifuged at 10,000 rpm for 10 minutes using a centrifuge, and the recovered precipitate was dispersed again in toluene to purify the quantum dots.

[0104] The light emission characteristics of the quantum dots obtained in this manner were measured. As a result, the emission wavelength was 536 nm, the half-value width of the light emission was 38 nm, and the internal quantum efficiency was 12%.

[0105] (Example 8)

[0106] After the same process 3 as in Comparative Example 7, 20 mg of anhydrous aluminum chloride (III), 2 mL of oleylamine, and 18 mL of 1-octadecene were mixed and degassed at 120°C for 2 hours to prepare an aluminum solution in which anhydrous aluminum chloride was dissolved, and 7 mL of the aluminum solution was added dropwise to the solution in which the core particles were synthesized by the same process 3 as in Comparative Example 7, while the temperature of the solution was maintained at 200°C and stirred at 200°C for 30 minutes to allow Al atoms to adsorb on the surface of the core particles. Afterwards, the same process as in the above process 4 was performed to obtain ZnSeTe / ZnS quantum dots with Al added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 517 nm, the half-value width of the luminescence was 35 nm, and the internal quantum efficiency was 20%.

[0107] (Example 9)

[0108] In the same manner as in Example 8, after the same process 3 as in Comparative Example 7, 20 mg of anhydrous manganese chloride (II), 2 mL of oleylamine, and 18 mL of 1-octadecene were mixed and degassed at 150° C. for 2 hours to prepare a solution in which anhydrous manganese chloride was dissolved. 3 mL of this solution was added dropwise to the solution in which the core particles were synthesized by the same process 3 as in Comparative Example 7, while the temperature of the solution was maintained at 200° C. and stirred at 200° C. for 30 minutes to adsorb Mn atoms on the core surface. Afterwards, the same process as in the above-mentioned process 4 was performed to obtain ZnSeTe / ZnS quantum dots to which Mn was added at the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 581 nm, the half-value width of the luminescence was 40 nm, and the internal quantum efficiency was 22%.

[0109] (Comparative Example 8)

[0110] ZnSeTe / ZnS core-shell quantum dots were synthesized under the same conditions as in Comparative Example 7, except that the synthesis temperature of the core particles in step 3 of Comparative Example 7 was changed to 280°C. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 530 nm, the half-value width of the luminescence was 44 nm, and the internal quantum efficiency was 10%.

[0111] (Comparative Example 9)

[0112] ZnSeTe / ZnS core-shell quantum dots were synthesized under the same conditions as in Comparative Example 7 except that the synthesis temperature of the core particles in step 3 of Comparative Example 7 was changed to 230° C. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 530 nm, the half-value width of the luminescence was 49 nm, and the internal quantum efficiency was 5%.

[0113] (Comparative Example 10)

[0114] In a 100mL three-necked flask, 20mL of 1-octadecene as a solvent, 6.5mL of oleic acid, and 3mg of anhydrous manganese chloride were added, and degassed at 120°C for 2 hours. After degassing, nitrogen was sealed in the flask, and the reaction was carried out in a state of isolating oxygen. In addition, 79mg of selenium powder and 96mg of tellurium powder were added to 20mL of trioctylphosphine, heated to 150°C and stirred to dissolve the selenium powder and tellurium powder, thereby preparing a selenium-tellurium solution. Under a nitrogen atmosphere, 10mL of the selenium-tellurium solution was mixed with 0.11mL of diethyl zinc, and the mixed solution was added dropwise to a flask heated to 250°C, and reacted at 250°C for 30 minutes to synthesize ZnSeTe core particles. For the obtained core particles, a ZnS shell layer was formed under the same conditions as in step 4 of comparative example 7. Thus, ZnSeTe / ZnS quantum dots with Mn atoms added to the core particles were obtained. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 596 nm, the half-value width of luminescence was 58 nm, and the internal quantum efficiency was 32%.

[0115] (Comparative Example 11)

[0116] The reaction was carried out under the same conditions as in Example 8, except that the amount of aluminum solution added in Example 8 was changed to 18 mL, thereby obtaining ZnSeTe / ZnS quantum dots with Al added to the core-shell interface. The luminescence properties of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 497 nm, the half-value width of the luminescence was 60 nm, and the internal quantum efficiency was 8%.

[0117] Table 2 shows the results of Examples 8 and 9 and Comparative Examples 7 to 11.

[0118] [Table 2]

[0119]

[0120] *Comparative Examples 7 to 9 had different reaction temperatures when forming core particles.

[0121] In Examples 8 and 9, as in Examples 1 to 7, quantum dots were obtained that could control the emission wavelength without adjusting the quantum dot diameter, and had high luminescence efficiency and good luminescence characteristics.

[0122] (Comparative Example 12)

[0123] (Step 5: Synthesis of CuInS2 core particles)

[0124] In a 100 mL three-necked flask, 10 mL of 1-octadecene as a solvent, 5 mL of 1-dodecyl mercaptan, 6.9 mg of copper chloride (I), 15.4 mg of indium acetate (III), and 40 mg of thiourea were added, and degassed at 100 ° C for 1 hour. After degassing, nitrogen was sealed in the flask, and the reaction was carried out in a state of isolating oxygen. The degassed solution was heated to 220 ° C and kept for 30 minutes to obtain CuInS2 core particles.

[0125] (Step 6: Synthesis of ZnS Shell)

[0126] 0.1 mL of diethyl zinc and 0.25 mL of 1-dodecyl mercaptan were mixed in 10 mL of 1-octadecene, and the mixed solution was added dropwise to the solution of CuInS2 core particles obtained in step 5 at a temperature of 250°C and stirred for 30 minutes. Thus, a CuInS2 / ZnS core-shell quantum dot solution was obtained.

[0127] Acetone was added to the quantum dot solution after the reaction in a 5-fold volume ratio to precipitate the quantum dots, and the solution was centrifuged at 10,000 rpm for 10 minutes using a centrifuge. The recovered precipitate was dispersed again in toluene to purify the quantum dots.

[0128] The light emission characteristics of the quantum dots obtained in this manner were measured. As a result, the emission wavelength was 658 nm, the half-value width of the light emission was 75 nm, and the internal quantum efficiency was 71%.

[0129] (Example 10)

[0130] After the same process 5 as in Comparative Example 12, 10 mg of anhydrous gallium chloride (III) and 20 mL of 1-octadecene were mixed and degassed at 150° C. for 1 hour to prepare a gallium solution in which anhydrous gallium chloride was dissolved. 1 mL of this solution was added dropwise to the solution in which the core particles were synthesized by the same process 5 as in Comparative Example 12, while the temperature of the solution was maintained at 200° C. and stirred at 200° C. for 30 minutes to allow Ga atoms to adsorb on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 6 was performed to obtain CuInS2 / ZnS core-shell quantum dots with Ga added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 632 nm, the half-value width of the luminescence was 59 nm, and the internal quantum efficiency was 74%.

[0131] (Example 11)

[0132] After the same process 5 as in Comparative Example 12, 1 mg of anhydrous ferric chloride (II), 2 mL of oleylamine, and 18 mL of 1-octadecene were mixed and degassed at 150 ° C for 1 hour to prepare a solution in which anhydrous ferric chloride was dissolved. 1 mL of this solution was added dropwise to a solution in which core particles were synthesized by the same process 5 as in Comparative Example 12, while the temperature of the solution was maintained at 200 ° C and stirred at 200 ° C for 30 minutes to adsorb Fe atoms on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 6 was performed to obtain CuInS2 / ZnS core-shell quantum dots with Fe added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and as a result, the emission wavelength was 689 nm, the half-value width of the luminescence was 77 nm, and the internal quantum efficiency was 72%.

[0133] (Comparative Example 13)

[0134] CuInS2 / ZnS core-shell quantum dots were synthesized under the same conditions except that the synthesis temperature of the core particles in step 5 of Comparative Example 12 was changed to 250°C. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 661nm, the half-value width of the luminescence was 91nm, and the internal quantum efficiency was 70%.

[0135] (Comparative Example 14)

[0136] CuInS2 / ZnS core-shell quantum dots were synthesized under the same conditions except that the synthesis temperature of the core particles in step 5 of Comparative Example 12 was changed to 190°C. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 655nm, the half-value width of the luminescence was 73nm, and the internal quantum efficiency was 50%.

[0137] (Comparative Example 15)

[0138] In a 100mL three-necked flask, 10mL of 1-octadecene as a solvent, 5mL of 1-dodecyl mercaptan, 6.9mg of copper chloride (I), 15.4mg of indium acetate (III), 40mg of thiourea and 0.5mg of anhydrous gallium chloride (III) were added, and degassed at 100°C for 1 hour. After degassing, nitrogen was sealed in the flask and the reaction was carried out in a state of being isolated from oxygen. CuInS2 core particles were obtained by heating the degassed solution to 220°C and keeping it for 30 minutes. For the obtained core particles, a ZnS shell layer was formed under the same conditions as in step 6 of comparative example 12. Thus, CuInS2 / ZnS quantum dots with Ga atoms added to the core particles were obtained. The luminescence characteristics of the quantum dots obtained in this way were measured, and as a result, the emission wavelength was 618nm, the half-value width of the luminescence was 89nm, and the internal quantum efficiency was 53%.

[0139] (Comparative Example 16)

[0140] The reaction was carried out under the same conditions as in Example 10, except that the amount of gallium solution added in Example 10 was changed to 3 mL, thereby obtaining CuInS2 / ZnS quantum dots with Ga added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 643 nm, the half-value width of the luminescence was 102 nm, and the internal quantum efficiency was 65%.

[0141] Table 3 shows the results of Examples 10 and 11 and Comparative Examples 12 to 16.

[0142] [Table 3]

[0143]

[0144] *Comparative Examples 12 to 14 had different reaction temperatures when forming core particles.

[0145] In Examples 10 and 11, as in Examples 1 to 9, quantum dots were obtained that could control the emission wavelength without adjusting the quantum dot diameter, and had high luminescence efficiency and good luminescence characteristics.

[0146] (Comparative Example 17)

[0147] (Step 7: Synthesis of AgInS2 core particles)

[0148] In a 100 mL three-necked flask, 10 mL of oleylamine as a solvent, 49 mg of silver acetate (I), 65 mg of indium acetate (III), 1.2 mL of 1-dodecyl mercaptan, and 12 g of thiourea were added, and degassed at 100 ° C for 30 minutes. After degassing, nitrogen was sealed in the flask, and the reaction was carried out in a state of isolating oxygen. AgInS2 core particles were obtained by heating the degassed solution to 150 ° C and holding it for 30 minutes.

[0149] (Step 8: Formation of Ga2S3 Shell Layer)

[0150] 80 mg of gallium (III) acetylacetonate and 24 mg of 1,3-dimethylthiourea were added to the solution of AgInS2 core particles obtained in step 7, and the solution was heated to 280°C and stirred for 30 minutes. Thus, an AgInS2 / Ga2S3 core-shell quantum dot solution was obtained.

[0151] Acetone was added to the quantum dot solution after the reaction in a 5-fold volume ratio to precipitate the quantum dots, and the solution was centrifuged at 10,000 rpm for 10 minutes using a centrifuge. The recovered precipitate was dispersed again in toluene to purify the quantum dots.

[0152] The light emission characteristics of the quantum dots obtained in this manner were measured. As a result, the emission wavelength was 596 nm, the half-value width of the light emission was 40 nm, and the internal quantum efficiency was 61%.

[0153] (Example 12)

[0154] After the same process 7 as in Comparative Example 17, 11 mg of bismuth chloride (III), 13 mg of tin iodide (II), 2 mL of oleylamine, and 18 mL of 1-octadecene were mixed and degassed at 150 ° C for 1 hour to prepare a solution in which bismuth chloride and tin iodide were dissolved. 1 mL of this solution was added dropwise to the solution in which the core particles were synthesized by the same process 7 as in Comparative Example 17, while the temperature of the solution was maintained at 150 ° C and stirred at 150 ° C for 30 minutes to adsorb Bi and Sn atoms on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 8 was performed to obtain AgInS2 / Ga2S3 quantum dots with Bi and Sn added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 578 nm, the half-value width of the luminescence was 36 nm, and the internal quantum efficiency was 62%.

[0155] (Example 13)

[0156] After the same process 7 as in Comparative Example 17, 10 g of molybdenum (III) chloride, 2 mL of oleylamine, and 18 mL of 1-octadecene were mixed and degassed at 150° C. for 1 hour to prepare a solution in which molybdenum chloride was dissolved. 2 mL of this solution was added dropwise to the solution in which the core particles were synthesized by the same process 7 as in Comparative Example 17, while the temperature of the solution was maintained at 150° C. and stirred at 150° C. for 30 minutes to allow Mo atoms to adsorb on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 8 was performed to obtain AgInS2 / Ga2S3 quantum dots with Mo added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 608 nm, the half-value width of the luminescence was 41 nm, and the internal quantum efficiency was 60%.

[0157] (Example 14)

[0158] After the same process 7 as in Comparative Example 17, 50 mg of anhydrous zinc acetate (II), 1 mL of oleylamine, 1 mL of oleic acid, and 18 mL of 1-octadecene were mixed and degassed at 150° C. for 1 hour to prepare a zinc solution in which anhydrous zinc acetate was dissolved. 2 mL of this solution was added dropwise to the solution in which the core particles were synthesized by the same process 7 as in Comparative Example 17, while the temperature of the solution was maintained at 150° C. and stirred at 150° C. for 30 minutes to allow Zn atoms to adsorb on the surface of the core particles. Afterwards, the same process as in the above-mentioned process 8 was performed to obtain AgInS2 / Ga2S3 quantum dots with Zn added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 588 nm, the half-value width of the luminescence was 38 nm, and the internal quantum efficiency was 77%.

[0159] (Comparative Example 18)

[0160] Except for changing the synthesis temperature of the core particles in step 7 of Comparative Example 17 to 180°C, AgInS2 / Ga2S3 core-shell quantum dots were synthesized under the same conditions.

[0161] The light emission characteristics of the quantum dots obtained through the above steps were measured. As a result, the emission wavelength was 599 nm, the half-value width of the light emission was 67 nm, and the internal quantum efficiency was 60%.

[0162] (Comparative Example 19)

[0163] AgInS2 / Ga2S3 core-shell quantum dots were synthesized under the same conditions except that the synthesis temperature of the core particles in step 7 of Comparative Example 17 was changed to 120°C. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 582nm, the half-value width of the luminescence was 59nm, and the internal quantum efficiency was 59%.

[0164] (Comparative Example 20)

[0165] In a 100mL three-necked flask, 10mL of oleylamine as a solvent, 49mg of silver acetate (I), 65mg of indium acetate (III), 1.2mL of 1-dodecyl mercaptan, 12g of thiourea and 5mg of anhydrous zinc acetate (II) were added, and degassed at 100°C for 30 minutes. After degassing, nitrogen was sealed in the flask, and the reaction was carried out in a state of isolation from oxygen. AgInS2 core particles were obtained by heating the degassed solution to 150°C and keeping it for 30 minutes. For the obtained core particles, a Ga2S3 shell layer was formed under the same conditions as in step 8 of comparative example 17. Thus, AgInS2 / Ga2S3 quantum dots with Zn atoms added to the core particles were obtained. The luminescence characteristics of the quantum dots obtained in this way were measured, and the results showed that the emission wavelength was 592nm, the half-value width of the luminescence was 70nm, and the internal quantum efficiency was 75%.

[0166] (Comparative Example 21)

[0167] Except that the amount of zinc solution added in Example 14 was changed to 3 mL, the reaction was carried out under the same conditions as in Example 14, thereby obtaining AgInS2 / Ga2S3 quantum dots with Zn added to the core-shell interface. The luminescence characteristics of the quantum dots obtained in this manner were measured, and the results showed that the emission wavelength was 608 nm, the half-value width of the luminescence was 50 nm, and the internal quantum efficiency was 70%.

[0168] Table 4 shows the results of Examples 12 to 14 and Comparative Examples 17 to 21.

[0169] [Table 4]

[0170]

[0171] *Comparative Examples 17 to 19 had different reaction temperatures when forming core particles.

[0172] Examples 12 to 14 are the same as Examples 1 to 11, and the emission wavelength can be controlled without adjusting the quantum dot diameter, and quantum dots with high luminescence efficiency and good luminescence characteristics are obtained.

[0173] The above embodiments are merely examples, and any technical solution having substantially the same structure and having the same function and effect as the technical concept described in the claims of the present invention is included in the protection scope of the present invention.

Claims

1. A quantum dot, which is a quantum dot as a crystalline nanoparticle phosphor, characterized in that: The quantum dot has a core-shell structure, which includes a core particle containing a first metal element and a shell layer containing a second metal element. A third metal element different from the first metal element and the second metal element exists at the interface between the core particle and the shell layer. The amount of the third metal element relative to the amount of the first metal element contained in the core particle is 10% or less by molar ratio, The third metal element is at least one selected from Al, Ga, Ge, Si, Bi, Cs, Sn, Li, Na, K, Ca, and Mg, The core particles are selected from CuInS2 and AgInS2.

2. The quantum dot according to claim 1, characterized in that The quantum dots do not contain Cd (cadmium).

3. A wavelength conversion material, characterized in that: It contains the quantum dots described in claim 1 or 2. A backlight comprising the wavelength conversion material according to claim 3. 5 . An image display device comprising the backlight according to claim 4 .

6. A method for producing quantum dots, which is a method for producing quantum dots as crystalline nanoparticle phosphors, wherein the quantum dots have a core-shell structure, wherein the core-shell structure includes a core particle containing a first metal element and a shell layer containing a second metal element, wherein the method is characterized in that: A step of forming the core particles; a step of adsorbing a third metal element different from the first metal element and the second metal element onto the surface of the core particle; and forming the shell layer on the third metal element on the surface of the core particle, In the step of adsorbing the third metal element, the amount of the third metal element relative to the amount of the first metal element contained in the core particles is set to 10% or less in terms of molar ratio, The third metal element is at least one selected from Al, Ga, Ge, Si, Bi, Cs, Sn, Li, Na, K, Ca, and Mg, The core particles are selected from CuInS2 and AgInS2.

7. The method for producing quantum dots according to claim 6, characterized in that: The reaction temperature of the step of adsorbing the third metal element is set to be equal to or lower than the reaction temperature of the step of forming the core particles.

Citation Information

Patent Citations

  • nanoparticles

    JP2010535262A

  • Quantum dot film, lighting device, and lighting method

    JP2013544018A

  • Preparation method of core-shell structure quantum dot

    CN102212363A

  • Light-emitting nano-particles and preparation method thereof

    CN106590624A

  • Core shell particles, production method for core shell particles, and film

    CN108350355A